Geochemistry of the Society and Pitcairn-Gambier mantle plumes: What they share and do not share. (1st August 2021) - Cordier, Carole; Delavault, Hélène; Chauvel, Catherine
Abstract: The South Pacific Superswell in Polynesia is associated with a large seismic mantle anomaly at depth, the Polynesian dome, and it is characterized by the volcanic activity of five different hotspots giving birth to the Marquesas, Society, Pitcairn-Gambier, Cook-Austral and Arago island chains. Here we present new isotopic and major and trace element data in basalts from two of these chains, the Society and Pitcairn-Gambier chains, in order to examine the similarities and differences of their mantle source regions. In the Society chain the entire geochemical diversity of the archipelago exists at the scale of individual islands with no systematic trend over time. In contrast, a clear geochemical dichotomy exists along the Pitcairn-Gambier chain between the old volcanoes ( Muru basalts from Mururoa, Fangataufa, Gambier, >5 My) and their younger counterparts ( Pitis basalts from Pitcairn Island and Seamounts, <1 My). The Muru group has high NbN /Nb* and Ce/Pb, low 87 Sr/ 86 Sr and define a steep trend in Nd-Hf isotopic space, features that call for old eclogite in their mantle source. The unradiogenic Pb isotopic ratios of Muru basalts, well below the values observed in HIMU ("high µ", or high 238 U/ 204 Pb) localities, are not easily explained by varying the age and composition of the eclogite and may call for the involvement of Pacific lower mantle in the source region. In contrast, the Pitis basalts share with the Society basalts low NbN /Nb* and radiogenic 87 Sr/ 86 Sr suggesting incorporation of continental material in their source region. While the Society source simply incorporates modern-like terrigenous sediments, the combination of low Ba/La, 143 Nd/ 144 Nd and 176 Hf/ 177 Hf and very high 208 Pb*/ 206 Pb* in Pitis basalts make the Pitis source unique and not sampled anywhere else on Earth. The Pitis source contains old, possibly Archean, material of unclear origin because it resembles neither modern lower continental crust nor modern pelagic sediments. Finally, the distribution of heterogeneities in the two mantle plumes is also very different: discrete filaments are randomly dispersed across the Society plume stem while eclogitic and continent-derived filaments are vertically separated under the Pitcairn-Gambier chain. By combining these results with those published for other Polynesian chains, we establish a snapshot of the composition, geometry and distribution of the crustal components present in the Polynesian dome.